Knowledge in Nutrition Among Pregnant Women in Apewosika, A Suburb Of Cape Coast: A Nexus in Pregnancy Out - Mensah, Nathan Kobina (Advances in Social Sciences Research Journal, 2014)
The study sought to find out the knowledge of nutrition among pregnant women in Apewosiksa, a suburb of Cape Coast. A sample of forty (40) women was obtained through the snowball sampling method. The objectives of the study were to find out the level of knowledge in nutrition and also knowledge in nutrition as evidenced by their eating of balanced diets, changes in meals during pregnancy to reflect the demands of pregnancy, ages of pregnancy; eating of a balanced diet and also the sources of their knowledge on nutrition. It came to light that forty percent of them lacked adequate knowledge in nutrition, 17.5% had no knowledge of the consequences of inadequate nutrition on pregnancy. Forty percent were teenagers; 40% of the women ate a balanced diet. Their sources of knowledge on nutrition were mainly through school and ante-natal care (47.5%). Remarkably, none of the respondents obtained her knowledge in nutrition through television. From the study it was realized that generally their level of knowledge in nutrition was inadequate hence the need for nutrition education is paramount.